(Studi Kajian Tematik) SOLUSI FENOMENA “MARRIAGE IS SCARY” PERSPEKTIF AL QUR’AN: Studi Kajian Tematik - Fauziyah, Sofi; Zainuddin, Ahmad; Masruri, Mukhid; Mufid, Miftara Ainul (Al - Tadabbur: Jurnal Ilmu Al-Qur'an dan Tafsir, 2025)
This study examines the phenomenon of "Marriage Is Scary" from the perspective of the Qur'an, reflecting the fears of many individuals, particularly the younger generation, towards the institution of marriage. The background of this research is based on the negative trends emerging on social media, which portray marriage as something frightening. The issues raised include the primary causes of this fear and the solutions offered by the Qur'an to address the phenomenon. The research method employed is a qualitative literature approach with thematic analysis of the Qur'anic verses that emphasize the importance of marriage. The findings indicate that marriage is viewed as a sacred and positive institution, emphasizing values of love, commitment, and responsibility among partners. By understanding the teachings of the Qur'an, individuals are expected to overcome their fears and see marriage as an opportunity to build harmonious and happy relationships